The Beast and the Dwelling House: On Sleeping Safely in Early Upper Canada - Bisha, Tim (Anthropologica, 2015)
The everyday dwelling house, an idea more often presumed than defined, finds sharp focus in a legal description of burglary. After acquiring a close categorical understanding of the burglar’s target, the article explores nuances of the crime, first by examining a burglary trial from early Upper Canada and, second, by contrasting burglary with social and legal practices relevant to duelling. Combining these threads, the dwelling house emerges as a core social and moral space, one that puts the crime of burglary and its implicit presumptions about community into deeper social perspective.